Breaking Glass: Toward a Gendered Analysis of Entrepreneurial Leadership. (27th April 2015) - Harrison, Richard; Leitch, Claire; McAdam, Maura; Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan
<x xml:space="preserve">Abstract</x> Despite recent expansion in the literature on entrepreneurial leadership, this has not been matched with the development of appropriate theoretical frameworks, theory building, and conceptual analyses, including the analysis of gender. In this paper, we provide the foundation for a more robust and extensive gendered study of entrepreneurial leadership, through a review of the entrepreneurial leadership literature and of the current debates on gender and leadership. On the basis of this, we propose a research agenda for the gendered analysis of the rapidly expanding interface between leadership and entrepreneurship, comprising three themes around which the future development of entrepreneurial leadership can be organized.